339 ACTIVATION OF SRC FAMILY TYROSINE KINASES AND PHOSPHORYLATION OF VAV1 DOWNSTREAM FROM MYD88 AND TRAF6 IN MURINE MACROPHAGES. Issue 1 (1st January 2007) - Daniel, A.; Haecker, H.; English, B. K.
Abstract : Background: We and others have reported that exposure of macrophages to LPS, CpG DNA, and other Toll-like receptor (TLR) ligands triggers the activation of multiple src family tyrosine kinases (SFKs) and the subsequent phosphorylation of vav1 . However, the mechanism(s) leading to the activation of SFKs downstream from TLRs are unknown. Purpose: We sought to determine whether SFK activation and vav1 phosphorylation occur downstream from two key signaling intermediates in the TLR cascade, MyD88 and TRAF6. Methods: We used two subclones of RAW 264.7 murine macrophages that have been engineered to express forms of MyD88 and TRAF6, respectively, that can be activated upon addition of the antibiotic coumermycin, leading to the production of inflammatory mediators, including tumor necrosis factor (TNF). Selective inhibitors of SFKs (PP1, PP2, SU6656) were used to test the involvement of these kinases in stimulation of TNF secretion downstream from MyD88 and TRAF6. Finally, we used immunoblotting to detect phosphorylation of vav1 on tyrosine 174 (an event known to be mediated by SFKs). Results: TLR-ligand-independent activation of either MyD88 or TRAF6 led to robust TNF secretion in these RAW subclones. Preincubation with any of the three SFK inhibitors resulted in dramatic reductions in the magnitude of TNF secretion by these cells (75-85% less in response to MyD88 activation; 50-60% less in response to TRAF6 activation). Finally, the tyrosine phosphorylation of vav1 on tyrosine 174 was detected within 10 to 20 minutes of coumermycin-induced activation of either MyD88 or TRAF6. Conclusions: Our data indicate that one or more SFKs are activated downstream from the TLR signaling cascade components MyD88 and TRAF6 in macrophages, leading to the phosphorylation of vav1 and playing an important role in the up-regulation of TNF production.